2008
DOI: 10.1007/s00429-007-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

The rat orbital and agranular insular prefrontal cortical areas: a cytoarchitectonic and chemoarchitectonic study

Abstract: Cytoarchitectonic characterization of borders is necessary for stereological studies (e.g., total cell number estimation), in which particular cortical areas have to be defined. In this study, cytoarchitectonic characteristics are described and illustrated for the rat ventral or orbital frontal cortical areas, i.e., the lateral-, ventrolateral-, ventral- and medial-orbital areas; and for the lateral frontal cortical areas, i.e., the agranular insular and the dorsolateral orbital cortical area. Each cytoarchite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 33 publications
8
70
1
Order By: Relevance
“…Other tissues do not show immunoreactivity (manufacturer's data sheet). Immunostaining with SMI-32 antibody has been used by several authors to build cytoarchitectural cortical maps (Sternberger and Sternberger, 1983;Voelker et al, 2004;Molnar and Cheung, 2006;Henny and Jones, 2008;Sia and Bourne, 2008;Van De Werd and Uylings, 2008). Immunostaining patterns of SMI-32 observed by us in different cortical areas match previous descriptions in these same cortical regions (Paxinos et al, 1999).…”
Section: Antibodies and Antibody Characterizationsupporting
confidence: 76%
“…Other tissues do not show immunoreactivity (manufacturer's data sheet). Immunostaining with SMI-32 antibody has been used by several authors to build cytoarchitectural cortical maps (Sternberger and Sternberger, 1983;Voelker et al, 2004;Molnar and Cheung, 2006;Henny and Jones, 2008;Sia and Bourne, 2008;Van De Werd and Uylings, 2008). Immunostaining patterns of SMI-32 observed by us in different cortical areas match previous descriptions in these same cortical regions (Paxinos et al, 1999).…”
Section: Antibodies and Antibody Characterizationsupporting
confidence: 76%
“…In line with these observations, animal studies demonstrated attenuated nicotine-seeking, but also attenuated cocaine-seeking, after inactivation of the insula (Di Pietro et al 2008;Forget et al 2010). In particular, the anterior part of the insula is interconnected with the NAc, amygdala and ventral mPFC (Van De Werd and Uylings 2008). Therefore, exposure to drug-related cues possibly leads to the retrieval of an interoceptive memory in the insula and thereby through its connections with the amygdala and anterior cingulate cortex to drug-craving (Naqvi and Bechara 2010).…”
Section: Insulasupporting
confidence: 53%
“…Moreover, there is a possibility that in the decision phase the AIC and OFC may functionally compete with each other directly or indirectly. Mutually inhibitory interaction between the AIC and OFC could be achieved by anatomical interconnection between them (Van De Werd and Uylings, 2008). Indirect competition could be achieved by opposite influences on other regions that receive projections from both AIC and OFC.…”
Section: Opposite Roles Of Aic and Ofc In Risky Decision Makingmentioning
confidence: 99%